The impact of elevated tropospheric ozone on grain quality of hybrid rice: A free-air gas concentration enrichment (FACE) experiment - Wang, Yunxia; Yang, Lianxin; Han, Yan; Zhu, Jianguo; Kobayashi, Kazuhiko; Tang, Haoye; Wang, Yulong (Field crops research, 2012)
► The impacts of projected future levels of tropospheric ozone concentration on grain quality of hybrid rice cultivar Shanyou 63 were determined under fully open-air field conditions. ► Ozone exposure enhanced the formation of chalky grains, while increased the head rice percentage. ► Elevated ozone concentration decreased eating and cooking quality of rice, but had positive influence on nutritive value of rice. Rising tropospheric ozone concentration is currently the most important air pollutant which suppresses plant growth and thus results in yield loss of agronomic crops. However little is known about ozone effects on grain quality of crops. Using a free-air gas concentration enrichment (FACE) facility for ozone fumigation in paddy rice (Oryza Sativa L.), a Chinese hybrid indica cultivar Shanyou 63 was exposed to either ambient or elevated ozone concentration (ca 23.5% above ambient) for two consecutive growth seasons from 2007 to 2008. Harvested grain samples were subjected to various quality tests. In both seasons, the brown, milled and head rice yield all reduced by elevated ozone concentration, with this reduction being greater in 2008 (17–22%) than in 2007 (8–19%). Ozone elevation caused small but significant decrease in brown rice percentage, but greatly increased head rice percentage by 8.8%. Chalky grain percentage increased (5.8%) due to ozone elevation, while chalkiness area and chalkiness degree remaining unchanged. Although the amylose concentration of rice grains was marginally reduced, starch pasting properties demonstrated that grains in elevated ozone concentration had lower breakdown (7.7%) and higher setback value (25.2%) and gelatinization temperature (0.9°C) than those grown in ambient conditions. Nutrition evaluation indicated that ozone exposure tended to increase the concentrations of protein and all mineral elements analyzed (i.e., K, Mg, Ca, Fe, Zn, Mn and Cu), but the contents of protein and mineral elements in harvested grains were unchanged or reduced. For most traits of grain quality, the year effect was significant, however, its interaction with ozone was not detected. Our results suggested that long-term exposure to ozone-enriched atmospheres projected in the coming a few decades not only caused serious reductions in yield, but also tended to produce the deleterious effects upon grain quality of hybrid Shanyou 63 in terms of appearance and eating/cooking quality.